Phytochemical compounds of Lilium ledebourii Bioss using bulb explants (Bangladesh Journal of Botany, 2018)
Lilium ledebourii Bioss is a wild species of Lilium, which grows naturally in Damash Mountains of Roodbar, Iran. Secondary metabolite synthesis in plants is one of the most important defensive mechanisms applied against various pathogens, and the quality and quantity of those materials depend on the species diversity, organs, habitat conditions, and different extraction methods. In this study, phytochemical compounds were measured quantitatively and qualitatively. Results showed the existence of secondary metabolites in the regenerated plants. Phenolic content was 5.198±0.17 mg in each extract. Radical trapping of the diphenyl-picryl hydrazyl test was 3.24 ± 0.52 mg/ml. Antioxidant activity based on reduced iron was 25.88 ± 1.47 mmol fe+2/g DW. Flavonoid content of L. ledebourii Bioss was 0.78±0.07 mgRE/G. Peroxidase and superoxide dismutase's enzymes activity in L. ledebourii Bioss was low. Also, in this study, the combination of saponin, cardiac glycosides, Steroids, Alkaloids and Terpenoid was seen qualitative in the L. ledebourii Bioss.